2020
DOI: 10.1002/cac2.12024
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 index, progesterone receptor expression, histologic grade and tumor size in predicting breast cancer recurrence risk: A consecutive cohort study

Abstract: Background:The 21-gene recurrence score (RS) assay has been recommended by major guidelines for treatment decision in hormone receptor (HR)-positive early breast cancer (EBC). However, the genomic assay is not accessible and affordable worldwide. Alternatively, an increasing number of studies have shown that traditional immunohistochemistry (IHC) can partially or even completely replace the role of the 21-gene genomic assay. Here, we developed and validated a predictive model (IHC3 model) combining the Ki-67 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
2
23
1
2
Order By: Relevance
“…Up to now, there were several models using clinical parameters to estimate the RS with TAILORx cutoffs [ 20 , 25 , 26 , 29 , 30 ]. Our nomogram has a similar discriminative ability with models developed by Lee et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there were several models using clinical parameters to estimate the RS with TAILORx cutoffs [ 20 , 25 , 26 , 29 , 30 ]. Our nomogram has a similar discriminative ability with models developed by Lee et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Ki-67 was not regularly recorded in the NCDB thus was not incorporated into their model, whereas our study demonstrated the importance of this biomarker in predicting high-risk RS. Recently, Zhang et al developed a model by using the Ki-67 index, PR expression, tumor grade, and tumor size with a predictive accuracy of 86.5%, which also had prognostic value [ 30 ]. However, it’s hard to perform a direct comparison between our two models because of the decision tree method they used.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with ER‐positive tumors are considered eligible for endocrine therapy. In contrast, patients with ER‐negative tumors are more likely to benefit from chemotherapy and usually have a worse outcome than the former [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there were several models using clinical parameters to estimate the RS with TAILORx cutoffs (20,25,26,29,30). Our nomogram has a similar discriminative ability with models developed by Lee et al (20,25).…”
Section: Discussionmentioning
confidence: 54%